2014
DOI: 10.1177/0363546514532227
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Magnetic Resonance Imaging UTE-T2* Mapping of Cartilage and Meniscus Healing After Anatomic Anterior Cruciate Ligament Reconstruction

Abstract: Background An anterior cruciate ligament (ACL) injury greatly increases the risk for premature knee osteoarthritis (OA). Improved diagnosis and staging of early disease are needed to develop strategies to delay or prevent disabling OA. Purpose Novel magnetic resonance imaging (MRI) ultrashort echo time (UTE)–T2* mapping was evaluated against clinical metrics of cartilage health in cross-sectional and longitudinal studies of human participants before and after ACL reconstruction (ACLR) to show reversible deep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
162
3
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 135 publications
(174 citation statements)
references
References 32 publications
(90 reference statements)
5
162
3
1
Order By: Relevance
“…Therefore, recent publications raised the evidence that using an ultrashort echo time sequence, T 2 * measurement might allow for the detection of early signs of degeneration, such as cartilage microcalcification in close proximity to the bone-cartilage interface. 29,30 Several limitations of our study have to be addressed. First, we did not perform subsequent scans to identify the time point when cartilage relaxation times return to the pre-run level.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, recent publications raised the evidence that using an ultrashort echo time sequence, T 2 * measurement might allow for the detection of early signs of degeneration, such as cartilage microcalcification in close proximity to the bone-cartilage interface. 29,30 Several limitations of our study have to be addressed. First, we did not perform subsequent scans to identify the time point when cartilage relaxation times return to the pre-run level.…”
Section: Discussionmentioning
confidence: 99%
“…UTE pulse sequences enable T2-and T2* weighted imaging of these tissues by using an extremely short TE 29 . There have been attempts to use UTE in evaluation of the deep layers of cartilage 30 , but its correlation with aspects of cartilage composition still needs to be validated 31 . In the past, when gradient inserts were required to obtain the necessary very short initial first echo sampling for effective T2* fitting of very short T2 species, such as tendon, ligament or cortical bone, it was thought that development of specialized MR equipment would be required for deployment of UTE to overcome technical challenges affecting image quality 32 .…”
Section: New Techniques In Imagingmentioning
confidence: 99%
“…Concomitant meniscal and chondral injuries are frequently encountered at the time of ACL reconstruction, but their longterm effect on outcomes is unclear [22][23][24] . As part of the MOON consortium, Cox et al found that Outerbridge grade-III and IV articular cartilage injuries and medial meniscal repair were associated with lower clinical scores, and knees with small, untreated lateral meniscal tears fared better at six years 25 .…”
Section: Risk Factors For Acl Outcomesmentioning
confidence: 99%